PENGARUH KEPEMILIKAN MANAJERIAL, INVESTMENT OPPORTUNITY SET (IOS), DAN DEBT COVENANT TERHADAP KONSERVATISME AKUNTANSI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Ryan Saptono; Etty Gurendrawati (Fakultas Ekonomi, Universitas Negeri Jakarta, 2014)
The purpose of this research is to see the influence of managerial ownership, Investment opportunity Set and Debt Covenant on Accounting Conservatism of manufacturing industry in Indonesian Stock Exchange. There are 27 manufacturing companies listed in Indonesian Stock Exchange used as samples for this research. This research used time series data from 2009 until 2011. The estimation result showed that managerial ownership, Investment opportunity Set and Debt Covenant had simultaneosly impact on Accounting Conservatism in manufacturing industry. The result also showed that managerial ownership had significant impact on Accounting Conservatism, but Investment opportunity Set and Debt Covenant had not significant impact. Keywords : managerial ownership, Investment opportunity Set, Debt Covenant and Accounting Conservatism